Drug sensitivity profiling of 3D tumor tissue cultures in the pediatric precision oncology program INFORM - Peterziel, Heike; Jamaladdin, Nora; ElHarouni, Dina; Gerloff, Xenia F.; Herter, Sonja; Fiesel, Petra; Berker, Yannick; Blattner-Johnson, Mirjam; Schramm, Kathrin; Jones, Barbara Christine; Reuss, David; Turunen, Laura; et al. (npj precision oncology, 2022)
The international precision oncology program INFORM enrolls relapsed/refractory pediatric cancer patients for comprehensive molecular analysis. We report a two-year pilot study implementing ex vivo drug sensitivity profiling (DSP) using a library of 75-78 clinically relevant drugs. We included 132 viable tumor samples from 35 pediatric oncology centers in seven countries. DSP was conducted on multicellular fresh tumor tissue spheroid cultures in 384-well plates with an overall mean processing time of three weeks. In 89 cases (67%), sufficient viable tissue was received; 69 (78%) passed internal quality controls. The DSP results matched the identified molecular targets, including BRAF, ALK, MET, and TP53 status. Drug vulnerabilities were identified in 80% of cases lacking actionable (very) high-evidence molecular events, adding value to the molecular data. Striking parallels between clinical courses and the DSP results were observed in selected patients. Overall, DSP in clinical real-time is feasible in international multicenter precision oncology programs.
Gesehen am 17.01.2023